HEYL Regulates Neoangiogenesis Through Overexpression in Both Breast Tumor Epithelium and Endothelium - Han, Liangfeng; Korangath, Preethi; Nguyen, Nguyen K.; Diehl, Adam; Cho, Soonweng; Teo, Wei Wen; Cope, Leslie; Gessler, Manfred; Romer, Lewis; Sukumar, Saraswati (Frontiers in Oncology, 2021)
Blocking tumor angiogenesis is an appealing therapeutic strategy, but to date, success has been elusive. We previously identified HEYL, a downstream target of Notch signaling, as an overexpressed gene in both breast cancer cells and as a tumor endothelial marker, suggesting that HEYL overexpression in both compartments may contribute to neoangiogenesis. Carcinomas arising in double transgenic Her2-neu/HeyL mice showed higher tumor vessel density and significantly faster growth than tumors in parental Her2/neu mice. Providing mechanistic insight, microarray-based mRNA profiling of HS578T-tet-off-HEYL human breast cancer cells revealed upregulation of several angiogenic factors including CXCL1/2/3 upon HEYL expression, which was validated by RT-qPCR and protein array analysis. Upregulation of the cytokines CXCL1/2/3 occurred through direct binding of HEYL to their promoter sequences. We found that vessel growth and migration of human vascular endothelial cells (HUVECs) was promoted by conditioned medium from HS578T-tet-off-HEYL carcinoma cells, but was blocked by neutralizing antibodies against CXCL1/2/3. Supporting these findings, suppressing HEYL expression using shRNA in MDA-MB-231 cells significantly reduced tumor growth. In addition, suppressing the action of proangiogenic cytokines induced by HEYL using a small molecule inhibitor of the CXCl1/2/3 receptor, CXCR2, in combination with the anti-VEGF monoclonal antibody, bevacizumab, significantly reduced tumor growth of MDA-MB-231 xenografts. Thus, HEYL expression in tumor epithelium has a profound effect on the vascular microenvironment in promoting neoangiogenesis. Furthermore, we show that HEYL expression in endothelial cells is essential for neoangiogenesis, both under normal physiological conditions and in cancer. Thus, HeyL-/- mice showed impaired vessel outgrowth in the neonatal retina, while the growth of mammary tumor cells E0771 was retarded in syngeneic HeyL-/- mice compared to wild type C57/Bl6 mice. Blocking HEYL’s angiogenesis-promoting function in both tumor cells and tumor-associated endothelium may enhance efficacy of therapy targeting the tumor vasculature in breast cancer.